Is the Reduction of the Length of Stay in Pre-Admission and Physiatry Inpatient for Traumatic Brain Injury Rehabilitation Cost-Effective? - Barbosa, Jorge; Interno de Medicina Física e de Reabilitação do Hospital de Curry Cabral (2013)
Objectives: In patients with Traumatic Brain Injury (TBI), the increase of the pre-admission inpatient Length Of Stay (LOS) (hospital acute care inpatient LOS in other specialties, before the admission in Physiatry) and the Physiatry ward inpatient LOS can not justify its inclusion or maintenance in inpatient rehabilitation. Therefore, it may not be cost-effective comparatively to ambulatory models. The main objective of this study was to evaluate the impact of the pre-admission and the Physiatry ward inpatient LOS in functionality gains obtained by patients with TBI. Material and Methods: Population: Patients admitted for TBI in the Physical Medicine and Rehabilitation (PMR) ward between 1/1/1996 and 31/12/2010 (n = 79). Inclusion criteria: TBI; pre-admission inpatient LOS < 6 months; PMR ward inpatient LOS >7 days. Exclusion criteria: neurologic and musculoskeletal impairments before the TBI; complications that would affect the rehabilitation program. Study sample n=64. The variation of several functionality parameters (dependent variables) were analysed based on the PMR ward admission and discharge records. The analyses used generalized linear statistical models: logistic regression, multiple linear regression and logistic ordinal regression, in the variables with binary, interval or ordinal scales, respectively. The independent variables of the model were gender, age and the pre-admission and PMR ward inpatient LOS. To test if there was improvement after inpatient rehabilitation in the PMR ward, the t parametric test for paired samples was applied. Results: Gender (female: 32.81%, male: 67.19%); mean age (34.73±14.64 years); mean LOS (pre-admission: 68.03±36.71 days, PMR ward: 46.55±29.23 days). The PMR ward inpatient LOS led to statistically significant gains (p < 6.54x10-2) in all the dependent variables. The Pre-Admission Inpatient LOS (PAILOS) had a nonlinear statistically significant influence in the PMR ward inpatient LOS (estimate PAILOS: 1.18, estimate PAILOS2: -5.92x10-3, p PAILOS: 9.17x10-3, p PAILOS2: 1.52x10-2). The reduction of the pre-admission inpatient LOS was associated with a more favourable evolution in 20 functionality variables, 10 of which with statistically significant influence (p < 0.12). The increase of the PMR ward inpatient LOS was significantly associated with greater gains in the FIM and Barthel scales (p < 4.31x10-3). Conclusions: The pre-admission inpatient LOS has a nonlinear influence on the PMR ward LOS and constitutes a parameter of functional outcome in rehabilitation. Its reduction is cost-effective in the TBI rehabilitation. Therefore, it is recommend to be taken into consideration when selecting patients to inpatient rehabilitation. The inpatient rehabilitation program leads to significant functionality gains and a higher duration is associated with greater gains. Keywords: Traumatic Brain Injury; Length of Stay; Physiatry; Cost-Benefit Analysis Rehabilitation.